Using Double-Contrast CT Arthrography to Confirm Suspected Dissociation of a Cemented Polyethylene Liner in the Setting of Revision Total Hip Arthroplasty: A Case Report. Issue 2 (April 2017) - Chauhan, Aakash; Fitzpatrick, Sean; Sciulli, Robert L.; Sotereanos, Nicholas G.; Sewecke, Jeffrey J.
Abstract : Case: A 67-year-old woman who underwent a re-revision of a total hip arthroplasty with a cemented polyethylene liner fell 14 months after surgery. The patient had symptoms of pain and weakness; however, clinical, laboratory, and radiographic evaluation did not disclose fracture, infection, osteolysis, or component migration. Liner dissociation was suspected, and a double-contrast computed tomography (CT) arthrogram confirmed failure at the cement-liner interface. She underwent additional revision surgery and was doing well at the 3-year follow-up. Conclusion: Double-contrast CT arthrography confirmed failure at the cement-liner interface and is an effective diagnostic tool in identifying suspected dissociations of cemented polyethylene liners.